ISPD Cardiovascular and Metabolic Guidelines in Adult Peritoneal Dialysis Patients Part II – Management of Various Cardiovascular Complications. Issue 4 (July 2015) - Wang, Angela Yee Moon; Brimble, K. Scott; Brunier, Gillian; Holt, Stephen G.; Jha, Vivekanand; Johnson, David W.; Kang, Shin-Wook; Kooman, Jeroen P.; Lambie, Mark; McIntyre, Chris; Mehrotra, Rajnish; Pecoits-Filho, Roberto
Cardiovascular mortality has remained high in patients on peritoneal dialysis (PD) due to the high prevalence of various cardiovascular complications including coronary artery disease, left ventricular hypertrophy and dysfunction, heart failure, arrhythmia (especially atrial fibrillation), cerebrovascular disease, and peripheral arterial disease. In addition, nearly a quarter of PD patients develop sudden cardiac death as the terminal life event. Thus, it is essential to identify effective treatment that may lower cardiovascular mortality and improve survival of PD patients. The International Society for Peritoneal Dialysis (ISPD) commissioned a global workgroup in 2012 to formulate a series of recommendation statements regarding lifestyle modification, assessment and management of various cardiovascular risk factors, and management of the various cardiovascular complications to be published in 2 guideline documents. This publication forms the second part of the guideline documents and includes recommendation statements on the management of various cardiovascular complications in adult chronic PD patients. The documents are intended to serve as a global clinical practice guideline for clinicians who look after PD patients. We also define areas where evidence is clearly deficient and make suggestions for future research in each specific area.